Pollen morphology of trees, shrubs and woody herbs of the coastal plain and the monsoon slopes of Dhofar (Sultanate of Oman) - Lippi, Marta Mariotti; Gonnelli, Tiziana; Raffaelli, Mauro (Webbia, 2007)
This paper describes the pollen morphology of the most common trees, shrubs and woody herbs growing in the coastal plain and the escarpment of Dhofar, a wide region in southern Oman. The plant habit and habitat are also reported.
Keywords: Botanique – Oman

Polygala moggii (Polygalaceae), a new species from Oman - Raffaelli, Mauro; Mosti, Stefano; Tardelli, Marcello (Webbia, 2007)
Polygala moggii grow in a coastal area near Hasik (eastern Dhofar). This new species, apart from its small size and small violet flowers, is also characterized by glabrous unwinged capsules and greenish petaloid sepals without evident nervation. For the characteristics of the sepals, this species resembles some other dwarf species from Somalia and Ethiopia, which have also a limited distribution.
Keywords: Botanique – Oman